Long-Term Exercise Reduces Formation of Tubular Aggregates and Promotes Maintenance of Ca2+ Entry Units in Aged Muscle - Boncompagni, Simona; Pecorai, Claudia; Michelucci, Antonio; Pietrangelo, Laura; Protasi, Feliciano (Frontiers in Physiology, 2021)
Tubular aggregates (TAs) in skeletal muscle fibers are unusual accumulation of sarcoplasmic reticulum (SR) tubes that are found in different disorders including TA myopathy (TAM). TAM is a muscular disease characterized by muscle pain, cramping, and weakness that has been recently linked to mutations in STIM1 and ORAI1. STIM1 and ORAI1 are the two main proteins mediating store-operated Ca2+ entry (SOCE), a mechanism activated by depletion of intracellular Ca2+ stores (e.g. SR) that allows recovery of Ca2+ from the extracellular space during repetitive muscle activity. We have recently shown that exercise triggers the formation of unique intracellular junctions between SR and transverse tubules (TTs) named Ca2+Entry Units (CEUs). CEUs promote co-localization of STIM1 with ORAI1 and improve muscle function in presence of external Ca2+. TAs virtually identical to those of TAM patients are also found in fast-twitch fibers of ageing male mice. Here, we used a combination of electron and confocal microscopy, western blotting, and ex vivo stimulation protocols (in presence or absence of external Ca2+) to evaluate the presence of TAs, STIM1-ORAI1 localization and expression, and fatigue resistance of intact extensor digitorum longus (EDL) muscles in wild type male adult (4 month old) and aged (24 month old) mice and in mice trained in wheel cages for 15 months (from 9 to 24 months of age). The results collected indicate that i) ageing causes STIM1 and ORAI1 to accumulate in TAs and ii) long-term exercise significantly reduced formation of TAs. In addition, iii) EDL muscles from aged mice exhibited a faster decay of contractile force than adult muscles, likely caused by their inability to refill intracellular Ca2+stores and iv) exercise in wheel cages restored the capability of aged EDL muscles to use external Ca2+ by promoting maintenance of CEUs. In conclusion, exercise prevented improper accumulation of STIM1 and ORAI1 in TAs during ageing, maintaining the capability of aged muscle to refill intracellular Ca2+stores via SOCE.